Age‐related changes in oral motor‐control strategies during unpredictable load demands in humans. (4th August 2020) - Almotairy, Nabeel; Kumar, Abhishek; Welander, Nadia; Grigoriadis, Anastasios
Abstract : To investigate age‐related changes in oral motor strategies in response to unpredictable load demands. Sixty‐five healthy children (aged 3–17 yr) were divided into five age‐groups based on their dental eruption stages and compared with a group of healthy adults (aged 18–35 yr). Each participant was asked to perform a standardized motor control task involving 'pulling' and 'holding' a force transducer with the anterior teeth. Different loads were attached to the force transducer in an unpredictable manner. The temporal force profile was divided into two time‐segments (an initial segment and a later segment). The peak force and peak force rate during the initial time‐segment, and the holding force and intra‐trial variability (coefficient of variation) during the later time‐segment, were measured. The results showed no differences in the peak force, peak force rate, holding force, and force variability in children compared with adults. However, the trends in the data evaluated using a segmented regression analysis showed that a breakpoint (abrupt change) consistently occurred in the late‐mixed dentition group (age 9–11 yr) for most of the outcome variables. The results indicate that while the motor control strategies in children appear to be similar to those in adults, there is a shift in the oral motor developmental trend during the late‐mixed dentition stage.